IMNCI Training at a Medical College in Gujarat-A feedback from the facilitators and Nursing Participants. - Misra S V; Baxi R K; Kotecha P V (Indian Association of Preventive and Social Medicine, 2011)
The paper describes the feedback from facilitators based on checklist used for monitoring clinical sessions during IMNCI (Integrated Management of Neonatal and Childhood Illness) trainings at a Medical College in Gujarat. Randomly selected checklists were analyzed for classification and problems faced by nursing staff participants. Ability to correctly classify and treat the illnesses ranged from 35% to 93%. The article also discusses the feedback from 55 participants (Nursing staff) drawn randomly from 25 batches of IMNCI trainings, gathered by VIPP (Visualization in Participatory Programmes) method applied at the end of the training. Suggestions to improve the quality of IMNCI trainings are recommended based on the findings.